2010
DOI: 10.2478/s11534-010-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of A-DLTS spectra of MOS structures with thin NAOS SiO2 layers

Abstract: Abstract:A set of MOS structures with thin SiO 2 layers prepared by nitric acid oxidation (NAOS) method was investigated using acoustic deep level transient spectroscopy (A-DLTS) to explain the role of annealing treatment (post-oxidation annealing (POA) and post-metallization annealing (PMA)) at different conditions on the distribution of interface states. The activation energies of interface states and the corresponding capture cross-section were calculated both from Arrhenius plots constructed for individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…As it has been demonstrated previously, acoustic waves are suitable not only for the investigation of materials directly related to acoustics, but also to study the properties of semiconductor structures [7] and glasses [8][9][10][11][12]. In the particular case of lithium and copper bearing phosphate glasses, the authors showed previously that there seems to be a close correlation between the activation energy for the ionic conduction and the activation energy of the acoustic relaxation process below the glass transition temperature [8][9].…”
Section: Introductionmentioning
confidence: 84%
“…As it has been demonstrated previously, acoustic waves are suitable not only for the investigation of materials directly related to acoustics, but also to study the properties of semiconductor structures [7] and glasses [8][9][10][11][12]. In the particular case of lithium and copper bearing phosphate glasses, the authors showed previously that there seems to be a close correlation between the activation energy for the ionic conduction and the activation energy of the acoustic relaxation process below the glass transition temperature [8][9].…”
Section: Introductionmentioning
confidence: 84%
“…28 P-Si MOS structures were fabricated on boron-doped p-type Si(100) wafers with 10-15 X cm resistivity. After RCA cleaning of the Si wafers and the removal of a native oxide layer, a thin oxide layer was formed by immersing the Si wafers in 70% HNO 3 aqueous solutions at 120 C. 29 After rinsing with ultrapure water, the wafers were divided to several parts and some parts were treated by postoxidation annealing (POA) in nitrogen performed for 1 h at 250 C (n MOS) or 700 C for 20 min (p MOS). Then, aluminum (Al) dots of 0.15 and 0.30 mm diameter were formed on all parts of prepared wafers, resulting in hAl/SiO 2 /Sii MOS diodes.…”
Section: Methodsmentioning
confidence: 99%
“…It should be mentioned that in simulations, the traps energy level, density, and distribution in the interface (D it ) are defined according to [22][23][24][25].…”
Section: Pixel Descriptionmentioning
confidence: 99%